A Numerical Study on Flow around Nonuniform Porous Fences - Long-Ming Huang; H. C. Chan; Jung-Tai Lee (Journal of Applied Mathematics)
The effects of a porous fence with a nonuniform porosity on flow fields are investigated numerically. First, an experiment with a non-uniform porous fence located in a wind tunnel is performed to obtain a reference data set. Then, a numerical model that utilizes the finite volume scheme with a weakly compressible-flow method to solve the continuity and momentum equations is developed. The numerical simulation is compared to experimental measurements for validation purposes. As a result, the numerical predictions show good agreements with the experimental data. Finally, the numerical investigations of the flow fields around porous fences with various combinations of upper and lower fence porosity are also presented. When the upper porosity is greater than the lower porosity, the Protection Index PI0.1, PI0.3 and PI0.5, representing the adverse sheltering effect, decreases compared to that of the uniform porous fence. When the upper porosity is less than the lower porosity, the PI0.5 increases and the variations of the PI0.1 and PI0.3, depend on the upper porosity, compared to that of the uniform porous fence. The results show that the porous fence with the upper fence porosity εU=0% and the lower fence porosity εL=30% gives the best sheltering effect among the porous fences in this study.